2016
DOI: 10.1093/nar/gkw1247
|View full text |Cite
|
Sign up to set email alerts
|

H3K27 acetylation activated-long non-coding RNA CCAT1 affects cell proliferation and migration by regulating SPRY4 and HOXB13 expression in esophageal squamous cell carcinoma

Abstract: Recently, long non-coding RNAs (lncRNAs) have been shown to have important regulatory roles in human cancer biology. In our study, we found that lncRNA CCAT1, whose expression is significantly increased and is correlated with outcomes in Esophageal Squamous Cell Carcinoma (ESCC). Consecutive experiments confirmed that H3K27-acetylation could activate expression of colon cancer associated transcript-1 (CCAT1). Further experiments revealed that CCAT1 knockdown significantly repressed the proliferation and migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
250
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 282 publications
(262 citation statements)
references
References 51 publications
10
250
1
1
Order By: Relevance
“…Accumulating documents have demonstrated that the dysregulation of lncRNAs are associated with tumorigenesis and progression of malignant tumors (18)(19)(20)(21)(22)(23). For instance, Zhou et al demonstrated that downregulation of lncRNA MEG3 mediated by DNMT3b contributed to nickel malignant transformation of human bronchial epithelial cells via modulating PHLPP1 transcription and HIF-1alpha translation (11).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating documents have demonstrated that the dysregulation of lncRNAs are associated with tumorigenesis and progression of malignant tumors (18)(19)(20)(21)(22)(23). For instance, Zhou et al demonstrated that downregulation of lncRNA MEG3 mediated by DNMT3b contributed to nickel malignant transformation of human bronchial epithelial cells via modulating PHLPP1 transcription and HIF-1alpha translation (11).…”
Section: Discussionmentioning
confidence: 99%
“…Hundreds of ESCC-associated lncRNAs were identified, some of which could be used as biomarkers for diagnosing or prognosing ESCC (14)(15)(16). ESCC-associated lncRNAs remain to be fully understood but research has progressed in this field: POU class 3 homeobox 3 (POU3F3) promotes the malignant progression of ESCC by binding the enhancer of zeste 2 polycomb repressive complex 2 subunit protein to promote the methylation of POU3F3 (17); colon cancer associated transcript 1 (non-protein coding) could modulate the histone methylation of the promoter of sprouty RTK signaling antagonist 4 by binding polycomb repressive complex 2 (PRC2) and suppressor of variegation 3-9 homolog 1 in the nucleus and promoted the expression of downstream target gene homeobox B13 by adsorbing microRNA-7 in the cytoplasm (18).…”
Section: Introductionmentioning
confidence: 99%
“…These data further verified that knockdown of SOX21-AS1 can induce p57 expression and SOX21-AS1 could play an important role in the cell cycle of LUAD. A large number of long non-coding RNAs have recently been reported to have a direct role in recruiting RNA-binding proteins to specific loci and in repressing gene expression in multiple cancers including NSCLC [23,27,53]. Thus, we hypothesize that SOX21-AS1 may repress p57 transcription via binding to related proteins, but further work is needed for confirmation.…”
Section: Discussionmentioning
confidence: 83%
“…Long noncoding RNAs (lncRNAs), which are longer than 200 nt in length [9,10], are a class of non-protein-coding RNA that have been demonstrated to play essential roles in cellular development and differentiation, in the modulation of apoptosis and in multiple biological processes [11][12][13][14][15]. More importantly, numerous studies have revealed that aberrant lncRNA expression is involved in a wide range of human diseases, particularly cancers [16][17][18][19][20][21][22][23][24]. Mounting evidence in recent years has demonstrated that lncRNAs, such as MALAT1 [25], LINC00473 [26], AGAP2-AS1 [27] play crucial roles in NSCLC development and progression.…”
Section: Introductionmentioning
confidence: 99%